Supplementary Material for the Article "Field, Capital, and Habitus: The Impact of Pierre Bourdieu on Bibliometrics" - Marco Schirone (University of Borås, 2022)
The full dataset of the review "Field, Capital, and Habitus: The Impact of Pierre Bourdieu on Bibliometrics" published in the journal Quantitive Science Studies (Appendix A), as well as the coding scheme (Appendix B), and a list of suggested readings based on the finding of the study (Appendix C).
Keywords: Pierre Bourdieu; Bibliometrics; Scientometrics; Quantitative Science Studies; Information Studies; Biblioteks- och informationsvetenskap